The influence of feedback on the change of the ball velocity of the set shot in the team handball - Pori, P.; Stirn, I.; Jeler, M.; Bon, M.; Sibila, M. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
Set shots are the most basic shots in the Team handball. In the present studies, we are interested in the ball velocity in the ejection phase in the conditions of the external influence in the form of feedback. The results showed that male students are prone to feedback from the radar, which can be associated with increased motivation to exercise. During training process, feedback from the radar could be valuable motivational tool for students.